Herschel-ATLAS/GAMA: how does the far-IR luminosity function depend on galaxy group properties? - Guo, Q.; Lacey, C.; Norberg, P.; Cole, S.; Baugh, C.; Frenk, C.; Cooray, A.; Dye, S.; Bourne, N.; Dunne, L.; Eales, S.; Ivison, R.J.; et al. (Oxford University Press, 2014)
We use the Herschel Astrophysical Terahertz Large Area Survey (H-ATLAS) Phase I data to study the conditional luminosity function of far-IR (250 μm) selected galaxies in optically selected galaxy groups from the Galaxy And Mass Assembly (GAMA) spectroscopic survey, as well as environmental effects on the far-IR-to-optical colour. We applied two methods, which gave consistent results for the far-IR conditional luminosity functions. The direct matching method matches H-ATLAS sources to GAMA/SDSS (Sloan Digital Sky Survey) galaxies, then links the optical counterparts to GAMA groups. The stacking method counts the number of far-IR sources within the projected radii of GAMA groups, subtracting the local background. We investigated the dependence of the far-IR (250 μm) luminosity function on group mass in the range 1012 < Mh < 1014 h−1 M⊙ and on redshift in the range 0 < z < 0.4, using a sample of 3000 groups containing H-ATLAS sources with GAMA redshifts over an area of 126 deg2. We find that the characteristic 250 μm luminosity, L*(250), increases with group mass up to Mh ∼ 1013 h−1 M⊙, but is roughly constant above this, while it increases with redshift at high group masses, but less so at low masses. We also find that the group far-IR luminosity-to-mass ratio L(250)/Mh increases with redshift and is higher in low-mass groups. We estimate that around 70 per cent of the 250 μm luminosity density in the local Universe is contributed by groups with Mh > 1012 h−1 M⊙. We also find that the far-IR-to-optical colours of H-ATLAS galaxies are independent of group mass over the range 1012 < Mh < 1014 h−1 M⊙ in the local Universe. We also compare our observational results with recent semi-analytical models, and find that none of these galaxy formation models can reproduce the conditional far-IR luminosity functions of galaxy groups.